In memoriam: Angus Maddison's Mission to Understand the World and its History through Numbers - Valli, Vittorio (The European Journal of Comparative Economics, 2010)
Angus Maddison's contribution to the analysis of long-run developments in the world economy has been monumental. His continuous cumulative work on an ever expanding data-set of national accounts and his in-depth analysis of changes in the main trends in the world's economic history has given us fundamental tools for a better understanding of past secular trends and future scenarios. His tentative estimates of total and per capita income in remote times must be considered important preliminary building stones in the process of cumulative learning. His main contributions to our knowledge of world economic changes, briefly surveyed in this paper, will be treasured by generations of scholars of comparative growth and development and of economic historians